Rethinking keberagamaan generasi Z: integrasi komunitas aktivis Dakwah Kampus melalui sikap toleransi untuk penguatan Moderasi Beragama - Muhammad Ihsanul Arief; Najmi Pakhruji Hidayatullah (Indonesian Journal of Islamic Religious Education, 2023)
The da'wah community in Indonesia has the power to influence religious life. The da'wah community provides social change, especially for students who will become leaders in the future. On the other hand, a big challenge for the Republic of Indonesia is the emergence of radical movements from the da'wah movement, which threatens stability. In this article, the author focuses on how religion is related to the tolerant attitude of the student missionary activist community at Lambung Mangkurat University and Antasari State Islamic University, South Kalimantan, to encourage the strengthening of religious moderation. The researcher also wants to explore how the da'wah community responds to aspects of life in the form of tolerance and attitudes towards culture that align with the spirit of strengthening moderate religious perspectives. This research was conducted through observation, interviews, and documentation related to the study's focus. The author's findings, who is actively involved in the da'wah community at PTU and PTI in South Kalimantan, regarding an attitude of tolerance that is in line with the religious typology, is included in the inclusive category. Other findings include integration between missionary activists through the imagination of brotherhood even though they do not know each other. This gives birth to patterns of religious attitudes that strengthen religious moderation.